Influences of Annealing on the Electrical Properties of Ba0,5Sr0,5TiO3 - Dwi Nugraheni Rositawati (Universitas Sanata Dharma, 2019)
The research aims to investigate influences of annealing on the electrical properties of Ba0,5Sr0,5TiO3. Ba0,5Sr0,5TiO3 material which was annealed at 900C for 1, 2 and 4 hours has better mechanical properties. It needs investigation for its electrical contribution, namely the correlation between grain and grain boundaries to values of resistance and capacitance. The changing of electrical properties was controlled by grain, grain boundary and the area between the sample and contact. The electrical properties of Ba0,5Sr0,5TiO3 were investigated by impedance spectroscopy in the room temperature. This method is able to separate the electrical and dielectric properties of the grain, grain boundary and the area between contact with the sample. ZsimpWin software was used to find out the equivalent electrical circuit, the resistance and capacitance value. It was observed that with the increase in annealing time the small grains resistance, the grain boundaries resistance, and the large grain capacitance value also increases. The resistance values of small grains and large grains were smaller than the grain boundaries resistance. The value of capacitance-resistance of the small grains and large grains were obtained values that tend to be smaller.